Tracking the Deep Biosphere through Time (Geosciences, 2021)
Deep biosphere research is at the scientific frontier of bio- and geo-related sciences, yet it is largely underexplored. In terms of volume, deep subsurface settings represent some of the largest microbial habitats on the planet, and the combined biomass of the deep biosphere encompasses the largest living reservoir of carbon, excluding land plants. However, the paleo-record of the deep biosphere is still largely uncharted and neglected. The aim of this book is to highlight current research on deep life through time and bring together researchers with various perspectives. The book presents a collection of scientific contributions that provide a sample of forefront research in this field. The contributions involve a range of case studies of deep ancient life in continental and oceanic settings, of microbial diversity in sub-seafloor environments, and of the isolation of calcifying bacteria, as well as reviews on clay mineralization of fungal biofilms and on the carbon isotope records of the deep biosphere. Deciphering the fossil record of the deep biosphere is a challenging task but, when successful, will unlock doors to life’s cryptic past.